2023
DOI: 10.1021/acsami.2c22871
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Sensors: Hydroxyl Decorated Silver Metal–Organic Frameworks for Detecting Cr2O72–, MnO4, Humic Acid, and Fe3+ Ions

Abstract: Anionic, acidic, and metal ions are common contaminants in water and cause serious concerns for human and aquatic life. With the goal of rapid detection of analytes, we herein design a new array of ligand 5-(4H-1,2,4-triazol-4yl)pyridin-3-ol-linked silver coordinated metal−organic frameworks Ag-MOFs as a promising sensor for Cr 2 O 7 2− , MnO 4− , humic acid (HA), and Fe 3+ ions down to the micro level. Furthermore, as evidenced by luminescence, excitation-emission matrix (EEM) spectroscopic, and PXRD measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Moreover, the LOD values for Fe 3+ , MnO 4 – , and Cr 2 O 7 2– are calculated to be 6.58, 4.53, and 2.73 μM, respectively. The observed K sv and LOD values are competitive or superior to those reported values of some other fluorescence MOFs. …”
Section: Resultsmentioning
confidence: 64%
“…Moreover, the LOD values for Fe 3+ , MnO 4 – , and Cr 2 O 7 2– are calculated to be 6.58, 4.53, and 2.73 μM, respectively. The observed K sv and LOD values are competitive or superior to those reported values of some other fluorescence MOFs. …”
Section: Resultsmentioning
confidence: 64%
“…4 ). By comparing the XRD patterns of Fe 3 O 4 and Fe 3 O 4 @SiO 2 @TAD-G2-SO 3 H, it can be confirmed that the ferrite core remains stable without undergoing any phase changes during the functionalization process 52 . The XRD patterns of the prepared Fe 3 O 4 @SiO 2 @TAD-G2-SO 3 H show distinct diffraction peaks at 2 θ = 30.2°, 35.4°, 43.7°, 56.6°, and 63.0°, corresponding to the (220), (311), (400), (422), (511), and (440) Miller planes of Fe 3 O 4 nanoparticles.…”
Section: Resultsmentioning
confidence: 80%
“…A summary of the sensing of Fe 3+ , Cr 3+ and Al 3+ ions using MOF materials is shown in Tables S6–S8 (ESI†), respectively. 52,59,89–120…”
Section: Resultsmentioning
confidence: 99%